Training on the Use of Handheld GPS and its Utilization in Vocational High Schools - Muhammad Rais Abidin; Ramli Umar; Ahyani Mirah Liani; Muh. Ansarullah S Tabbu; Jeddah Yanti (PT. Global Research Collaboration, 2024)
Training on Using Handheld GPS at SMK Negeri 05 Barru aims to increase students' knowledge and skills in utilizing Global Positioning System (GPS) technology for navigation and mapping purposes. This training includes an introduction to basic GPS functions, operating techniques, as well as practical applications in education and industry. The methods used include theory sessions and direct practice, so that students can understand comprehensively. The results of the training show an increase in students' understanding of the use of GPS, which is expected to support their competence in facing challenges in the world of work. In addition, this training encourages students to be more active in exploring technology and innovation in relevant fields. It is hoped that similar activities can be carried out on an ongoing basis to optimize the technical skills of students at SMK Negeri 05 Barru.